THE REGULATION OF ISSUES OF PERFORMING BAPTISM AND OCCASIONAL CHURCH RITUALS IN THE CONTEXT OF RUSSIA-ARMENIA INTERFAITH RELATIONS (1828–1905) - Blohin, Vladimir Sergeevic (History, Archeology and Ethnography of the Caucasus, 2020)
The paper attempts to analyze the regulation of cases, in which Orthodox people would ask to perform baptism and other religious rituals priests of the Armenian Apostol Church, while followers of the Armenian faith – priest of the Orthodox Church, without changing one’s religious affiliation. It has been determined that such situations occurred due to compelling reasons, which entailed negative consequences of the state-legal, church-canonical, everyday nature and led to the separation of families on a confessional basis. For instance, the fact that a child born to an Orthodox spouse was baptized by an Armenian priest was regarded as “leading astray from Orthodoxy”, even if a newborn was seriously ill. If an Armenian child was baptized according to the Orthodox order, then formally he became a member of the Orthodox Church, while his parents continued to belong to the Armenian Apostol Church. The study uses legislative sources and materials of record-keeping of the National Archive of Armenia and the Russian State Historical Archive. Methodologically, the article is based on systematization, classification and analysis of these documents. The comparative-historical method has been applied to compare facts and events, identify the process of regulating church practical situations and determine their role in the history of Russian-Armenian confessional relations. It has been concluded that, firstly, the incorporation of Eastern Armenia and the Armenian Apostolic Church into Russia led to the emergence of issues of a church-practical nature, which should have been regulated on the basis of the Russian legislation by the governing bodies of the both churches. Secondly, the decree of the Echmiadzin Synod of 1854, which was in force until 1899, granted Armenian priests the right to perform all church sacraments in relation to Armenian children baptized in infancy according to the Orthodox order, provided that the parents, being of Armenian religion, did not give a written commitment to educate them in the Orthodox faith. Thirdly, the patronizing policy of the empire in relation to Orthodoxy and the dominant position of the Russian Church led to complications in the relationship between the Orthodox clergy and the clergy of the Armenian Church. In cases where representatives of the both churches had the initial equal rights to perform public church rituals (for example, the rite of consecration of water on the feast of the Epiphany of our Lord within one city), priority – an¬d, in some cases (as, for example, in 1858 in Astrakhan) – the exclusive right, – was granted to the Russian Orthodox Church.